Synthesis of dihydroquinoxaline-2(1H)-ones via palladium-catalyzed intramolecular C–N bond formation. Issue 29 (20th July 2016) - Areephong, Jetsuda; Huo, Bright; Mbaezue, Ifenna I.; Ylijoki, Kai E.O.
Graphical abstract: Highlights: Pd-catalyzed C–N coupling for heterocycle preparation. NaI-catalyzed SN 2 substitution with alkyl and aryl amine nucleophiles. Divergent synthesis of aminoalcohols. Highly-substituted dihydroquinoxaline-2(1 H )-one synthesis. Abstract: A new strategy for the preparation of highly-substituted dihydroquinoxaline-2(1 H )-ones is reported. The strategy harnesses a divergent NaI-catalyzed amine substitution of mesylates to prepare a range of sterically hindered amidoamine substrates. These substrates are then subjected to Pd(dba)2 /P( t Bu)3 mediated cyclization. The preparation of amidoalcohol substrates occurs with reasonable yields (40–84%), with lower yields being obtained with aromatic and bulky amines. Palladium-catalyzed intramolecular C–N bond formation is slow, requiring 10 mol % catalyst loadings for complete conversion in 16 h. All substrates cyclized with reasonable yields (48–73%).